The effects of synbiotic supplementation on markers of insulin metabolism and lipid profiles in gestational diabetes: a randomised, double-blind, placebo-controlled trial. Issue 8 (29th September 2016) - Ahmadi, Shahnaz; Jamilian, Mehri; Tajabadi-Ebrahimi, Maryam; Jafari, Parvaneh; Asemi, Zatollah
Abstract: To the best of our knowledge, data on the effects of synbiotic supplementation on markers of insulin metabolism and lipid concentrations in patients with gestational diabetes mellitus (GDM) are scarce. The aim of the current study was to determine the effects of synbiotic supplementation on markers of insulin metabolism and lipid profiles in GDM patients. In total, seventy patients with GDM aged 18–40 years were assigned to two groups – the synbiotic group ( n 35) and the placebo group ( n 35) – in this randomised, double-blind, placebo-controlled trial. Patients in the synbiotic group received a daily capsule that contained three viable and freeze-dried strains: Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium bifidum (2×10 9 colony-forming units/g each) plus 800 mg inulin for 6 weeks. Fasting blood samples were collected at the beginning and week 6 to quantify related markers. After 6 weeks of intervention, compared with the placebo, synbiotic supplementation led to a significant decrease in serum insulin levels (−1·5 (sd 5·9) v. +4·8 (sd 11·5) µIU/ml, P =0·005), homoeostatic model assessment for insulin resistance (−0·4 (sd 1·3) v. +1·1 (sd 2·7), P =0·003) and homoeostatic model assessment for β cell function (−5·1 (sd 24·2) v. +18·9 (sd 45·6), P =0·008) and a significant increase in quantitative insulin sensitivity check index (+0·01 (sd 0·01) v. −0·007 (sd 0·02), P =0·02). In addition, synbiotic intake significantly decreased serum TAG (−14·8 (sd 56·5) v. +30·4 (sd 37·8) mg/dl, P <0·001) and VLDL-cholesterol concentrations (−3·0 (sd 11·3) v. +6·1 (sd 7·6) mg/dl, P <0·001) compared with the placebo. Overall, the results of this study demonstrate that taking synbiotic supplements for 6 weeks among patients with GDM had beneficial effects on markers of insulin metabolism, TAG and VLDL-cholesterol concentrations.